Effects of a combination of arginine silicate complex and magnesium biotinate on the corneal phototoxic effect of UV exposure in rats - Şahin, Nurhan; Orhan, Cemal; Tuzcu, Mehmet; Komorowski, James; Ojalvo, Sara; Sylla, Sarah; Şahin, Kazım (Wiley, 2020)
[Abstract Not Available]
Annual Meeting on Experimental Biology -- APR 04-07, 2020 -- San Diego, CA